Desain Perencanaan Program Sanitasi Total Berbasis Masyarakat (STBM) Dan Evaluasi Dampaknya Terhadap Penurunan Penyakit Berbasis Lingkungan - Indri Trisalowika Purba; Jehan Dangio; Nikita Manengkey; Robintang Situmorang; Keirin Bawues; Tesalonika Mokoagow; Miyuki Kowaas; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Environmental-based diseases remain a major public health issue associated with unsafe drinking water, inadequate sanitation, poor hygiene behavior, improper household waste management, and unsafe domestic wastewater disposal. Community-Based Total Sanitation, known in Indonesia as Sanitasi Total Berbasis Masyarakat or STBM, is a community empowerment approach designed to change hygiene and sanitation behavior through five pillars. This article aims to develop an STBM program planning design and an impact evaluation model for reducing environmental-based diseases, particularly diarrhoeal disease. This study used a narrative review method by analyzing national regulations, official guidelines, global WASH reports, and recent scientific literature. The proposed program design includes situation analysis, multisectoral advocacy, community triggering, household mentoring, strengthening sanitation facilities, monitoring, verification, and impact evaluation. The evaluation model uses process, output, outcome, and impact indicators, with diarrhoea incidence as the main measurable health indicator. The findings indicate that an integrated STBM program supported by community participation, valid baseline data, and periodic evaluation can strengthen the prevention of environmental-based diseases. This article recommends implementing STBM as a sustainable community-based public health intervention rather than a short-term sanitation activity.